IMPLEMENTASI SISTEM INTERLOCK ONLINE MONITORING PADA OZONATOR DALAM UPAYA PENGENDALIAN EMISI - Made Dwi Elistina; Wayan Sukadana (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Universitas Mahasaraswati Denpasar, Bali, Indonesia, 2024)
The use of ozone has been widely applied across various sectors, proving its benefits, including as a disinfectant in drinking water treatment. Unlike chlorine, ozone does not produce harmful by-products like carcinogenic trihalomethanes. Ozone technology is also environmentally friendly and regarded as a future green chemical. This study aims to implement an interlock system in the online monitoring of an ozonator to control emissions. Results show that installing an online monitoring tool in the final product tank allows continuous ozone concentration tracking in water. The system includes an interlock feature that automatically halts water treatment and production if ozone levels exceed the standard limits. The monitoring device comprises ozone sensors, a prominent instrument panel, and connects to a PLC to control the interlock system. With this system, manual checks using a colorimeter are reduced to once per shift, cutting LB3 waste by 0.017 tons per semester.